Penundaan Eksekusi Hukuman Mati dalam KUHP Baru: Analisis Dampak Hukum, Sosial, dan Psikologis - Salma Daja; Muhammad Irayadi (Decisio: Jurnal Ilmiah Hukum, 2025)
This study explores the legal, social, and psychological impacts of delaying the execution of death sentences under the new Indonesian Criminal Code (KUHP). The introduction of a 10-year probationary period for death row inmates has raised legal uncertainties regarding execution timelines and potential changes in sentencing. The research highlights the psychological strain and potential human rights violations that long delays may cause for those awaiting execution, leading to significant concerns within the criminal justice system. Additionally, it examines how this delay influences the integrity of the legal framework in Indonesia. The study uses a qualitative method with a normative legal approach, focusing on analyzing regulations and interpreting legal norms in practice. Data were collected through an in-depth literature review of legal documents and previous studies.The findings indicate that the delay in execution contributes to a lack of certainty in the legal process, which affects both the detainees' mental health and the public’s trust in the justice system. Psychological effects on death row inmates, such as severe distress and mental deterioration, are significant, while the legal impact shows the need for clearer regulations to ensure justice and prevent human rights violations. The study concludes that reforming execution timelines and legal processes is crucial for improving the fairness and effectiveness of the Indonesian criminal justice system.